Model Outing Class Pada Pembelajaran PAI: Upaya Sistematis Membangun Karakter Islami - Widadi, Ahmad Setyo; Fadhila, Milatika Luthfi; Soraya, Irma; Kurjum, Mohammad (Prodi Pendidikan Keagamaan Islam, 2025)
Education plays a vital role in shaping human character and morality in accordance with Islamic values and national education goals. To achieve these objectives, appropriate learning strategies are essential. SD Islam Darul Falah Tambak Banyumas implements the outing class strategy (learning outside the classroom) as an innovative approach in teaching Aqidah and Adab. This study aims to examine the implementation, impact, and the supporting and inhibiting factors of this strategy for third-grade students. The research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. Data analysis involves data reduction, presentation, and conclusion drawing. The findings reveal that the implementation of outing class is aligned with relevant lesson themes and is often integrated with other subjects. The strategy positively influences students’ motivation and comprehension, although challenges such as teacher readiness and logistical constraints remain. In conclusion, outing class is an effective method for teaching Aqidah and Adab when supported by thorough planning.